Parameters which predict detrusor overactivity after adjustable trans obturator male system (ATOMS) implant. - Miguel Vírseda-Chamorrro; Sonia Ruiz-Graña; Jesús Salinas-Casado; Javier Angulo Cuesta (Continence Reports)
Aims:: To evaluate which parameters predicted the presence of detrusor overactivity after ATOMS implant in patients who had post prostatectomy urinary incontinence (PPI). Method:: We carried out a prospective study in 56 patients submitted to ATOMS implant for PPI. The study consisted of a clinical and urodynamic record before and after ATOMS implantation. We built a multivariate model to find out which variables independently influenced postoperative DO and a ROC curve to decide the best cut-off value. Results:: We found that the preoperative variables were age, detrusor pressure at maximum flow rate (PQmax) the urethral resistance parameter URA and the bladder contractility index (BCI) and the postoperative variables were, the number of ATOMS adjustments, cystometric bladder capacity, bladder compliance, maximum detrusor pressure, PQmax, bladder outflow obstruction index, URA and the presence of acontractile detrusor. The multivariate model showed that the only independent variables were age (inversely related with the presence of postoperative DO), and URA (directly related). The cut-off point of URA was established at 10. 5 cm H2O. Conclusions:: the degree of postoperative resistance measured by the URA parameter and age were the two factors that independently influenced the presence of postoperative DO. It is possible that these parameters are related to the reaction of detrusor muscle to the increase in postoperative urethral resistance.